A sociolinguistic analysis of language style in Ghostbusters: Frozen Empire (2024) film - Zenanda, Agiska Zerpi; Rahayu, Famala Eka Sanhadi (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2025)
This study investigates the use of language styles in the film Ghostbusters: Frozen Empire (2024) through the lens of Martin Joos’s theoretical framework, which classifies language into five distinct styles: frozen, formal, consultative, casual, and intimate. Grounded in sociolinguistic theory, the research examines how language serves as a reflection of social identity, interpersonal relationships, and the communicative context in which it is used. The film was selected as the research object due to its rich portrayal of interactions that span multiple genres, including family, comedy, and supernatural adventure, making it particularly suitable for examining variations in communication. A descriptive qualitative approach was employed, with data derived from the dialogues of the main characters. Data collection involved detailed observation, identification of key scenes, and systematic categorisation of dialogues according to Joos’s language style framework. Data analysis followed Miles and Huberman’s model, encompassing the processes of data reduction, data display, and conclusion drawing. The primary objectives of this study are to describe the range of language styles utilised by the main characters and to identify which style is most dominant within the film’s interactions. The findings are anticipated to provide both theoretical contributions to sociolinguistic scholarship and practical benefits for audiences, enhancing their understanding, appreciation, and critical engagement with language use in cinematic narratives. Ultimately, this study offers insights into how stylistic choices in film dialogue shape social meaning, influence audience perception, and illuminate the dynamic interplay between language, context, and social identity in contemporary media.